2023
DOI: 10.3390/ijms24043663
|View full text |Cite
|
Sign up to set email alerts
|

Size-Exclusion Chromatography Combined with Ultrafiltration Efficiently Isolates Extracellular Vesicles from Human Blood Samples in Health and Disease

Abstract: There is still a need for an efficient method for the isolation of extracellular vesicles (EVs) from human blood that provides a reliable yield with acceptable purity. Blood is a source of circulating EVs, but soluble proteins and lipoproteins hamper their concentration, isolation, and detection. This study aims to investigate the efficiency of EV isolation and characterization methods not defined as “gold standard”. EVs were isolated from human platelet-free plasma (PFP) of patients and healthy donors through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A study with application of normoxic and hypoxic conditions found no effect of the conditions on particle concentration, apart from healthy subjects in normoxic conditions, in whom a statistically significant increase in the number of EVs was detected [ 43 ]. In another study with healthy individuals and patients with idiopathic inflammatory myopathies, the healthy people had on average a lower concentration of EVs than the patients [ 44 ] ( Table III ).…”
Section: Discussionmentioning
confidence: 99%
“…A study with application of normoxic and hypoxic conditions found no effect of the conditions on particle concentration, apart from healthy subjects in normoxic conditions, in whom a statistically significant increase in the number of EVs was detected [ 43 ]. In another study with healthy individuals and patients with idiopathic inflammatory myopathies, the healthy people had on average a lower concentration of EVs than the patients [ 44 ] ( Table III ).…”
Section: Discussionmentioning
confidence: 99%
“…Conzelmann C. et al also used UF (100 kDa commercial filters) to purify saliva EVs in a study focused on EV involvement in anti-Zika virus activity. 48 In addition, UF was commonly combined with other isolation methods such as UC, SEC and FFF as an additional step to concentrate the sample by reducing its volume and or perform additional purification to eventually obtain EVs from cell culture medium [49][50][51] as well as biofluids such as urine, 43,52 plasma or serum, 47,53,54 stool, 53 semen, 55 saliva, 48 cerebrospinal fluid, 56 peritoneal dialysis effluent, 57 bronchoalveolar lavage fluid, 58 and stromal vascular fraction. 59 In a recent report, an asymmetric DF method for EV isolation from biological fluids (plasma, urine) and cell culture media was introduced for the first time (Fig.…”
Section: Normal Flow Filtrationmentioning
confidence: 99%
“…In addition, UF was commonly combined with other isolation methods such as UC, SEC and FFF as an additional step to concentrate the sample by reducing its volume and or perform additional purification to eventually obtain EVs from cell culture medium 49–51 as well as biofluids such as urine, 43,52 plasma or serum, 47,53,54 stool, 53 semen, 55 saliva, 48 cerebrospinal fluid, 56 peritoneal dialysis effluent, 57 bronchoalveolar lavage fluid, 58 and stromal vascular fraction. 59…”
Section: Normal Flow Filtrationmentioning
confidence: 99%
“…EVs are produced by various types of cells and are consistently found in body fluids, including blood, saliva, urine, semen, breast milk, malignant ascites, and cerebrospinal fluid, as well as tissue and cell culture media. , Up to the present, researchers in relevant fields have proposed several predominant techniques for isolating EVs from complex biological samples (Figure ). These methods include ultracentrifugation (UC), differential ultracentrifugation (DC), , density gradient centrifugation (DGC), size exclusion chromatography (SEC), membrane filtration, microfluidic platforms, flow field-flow fractionation, affinity-based techniques, and immunomagnetic bead enrichment. , Among these methods, UC is regarded as the gold standard, and the combination of these techniques has been documented to yield high-quality EVs. While each of these methods presents its own set of advantages and disadvantages, based on the scope detailed in the present study, these isolation approaches can effectively purify EVs from complex biological samples to a certain degree. This enables both qualitative and quantitative analysis of the biomolecules carried by them.…”
Section: The Research Of Glycosylation In Evsmentioning
confidence: 99%